Formulasi dan Evaluasi Sediaan Topikal Nanogel Daun Kipahit (Tithonia diversifolia) dan aktivitas sebagai Antimikroba - Faza Fauzan Azima; Vera Estefania Kaban; Astriani Natalia Br Ginting (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Candida albicans is a fungal microorganism that can cause candidiasis and requires the development of alternative therapies derived from natural products. Bitter leaf (Tithonia diversifolia) contains bioactive compounds such as flavonoids, alkaloids, and tannins that have potential antifungal activity. This study aimed to formulate and evaluate a nanogel containing ethanol extract of Tithonia diversifolia leaves and to assess its antifungal activity against Candida albicans. The extract was obtained through maceration using 70% ethanol and formulated into nanogels using a modified emulsification-diffusion method at concentrations of 5%, 10%, and 15%. The formulations were evaluated for organoleptic properties, homogeneity, pH, spreadability, viscosity, particle size, and antifungal activity using the agar well diffusion method. The results showed that all nanogel formulations exhibited good physical characteristics and met the requirements for topical application. Particle size analysis revealed sizes ranging from 755.75 to 847.29 nm, indicating that all formulations met the criteria for nanoparticulate systems. All formulations demonstrated inhibitory activity against the growth of Candida albicans, with inhibition tending to increase as the extract concentration increased. The incorporation of bitter leaf extract into a nanogel system may improve the stability and delivery of bioactive compounds compared with conventional formulations. Therefore, the ethanol extract nanogel of Tithonia diversifolia leaves has the potential to be developed as a natural-based topical antifungal formulation.